Friendly burger manufacturer / Yanadiana Yakinol... [et al.] - Yakinol, Yanadiana; Saman, Noorizan Biti; Omar, Marzatun Najiha; Lingkuman, Annie; Muhuddin, Mudzah (Faculty of Administrative Science and Policy Studies, 2008)
Burger was introduced in our country by the restaurant which provided the fast food for the people. For beginning it was popular in the cities. Nowadays, the burger has been accepted by people especially youths. The burger is made from the blended beef and mixed with the ingredients then it will be shaped to the burger. It can be made by the mutton, beef, and chicken. In Malaysia the most popular burger are beef and chicken. The food ACT 1985 is stated that the burger must be consist not less 65% beef and cannot contains less than 1. 7% nitrogen in organic combination and can’t be contains of more than 30% fat (ACT 147). After we made a discussion, we have choose to open the manufacturing of burger as our business, since it has the potential in Malaysia namely burger based on beef, and chicken.